Analisis Asuhan Keperawatan Pasien Leukemia dengan Pemberian Terapi Musik pada Masalah Keperawatan Nyeri Akut - Prianugraha, Kadek Andal Martadi; Astriani, Ni Made Dwi Yunica; Dewi, Putu Indah Sintya (Journal of Telenursing (JOTING), 2024)
This study aims to explain nursing care by providing music therapy for acute pain nursing problems in leukemia patients. The method used is to analyze the nursing care that has been provided, namely music therapy to treat pain in leukemia patients. The results of the study showed that there was a decrease in pain levels in leukemia patients before and after the music therapy intervention was given. The music the patient listens to helps the patient feel relaxed and calm, so that after listening to music he can calm himself down and forget for a moment the pain or pain the patient is experiencing. In conclusion, even though music does not affect the disease itself, this therapy makes patients forget about the condition and pain by focusing on breathing and the music they listen to, even if only for a moment. Keywords: Leukemia, Pain, Music Therapy